Implementasi E-Government Kulon Progo: Inovasi Dinas Kesehatan Melalui Aplikasi BumilKU 2019 - Rico Kurniawan; Muhammad Eko Atmojo (Sospol : Jurnal Sosial Politik, 2020)
Based on Indonesia committement on sustainable development, health improvement is a prominent issue. As an implementation of public service innovation, the Kulon Progo Regional Government through the Health Office plays a role in improving the quality of health services for pregnant women by creating the BumilKU application. Considering the importance of measuring the role of organizational performance on aspects of public service quality which refers to the e-government paradigm, this study aims to explain the performance of local governments in providing services to pregnant women through the BumilKU application. The data used in this study came from interviews, document studies, and literature studies related to research discussions. Based on several indicators of organizational performance measurement, pregnant women's health services utilize and use the BumilKU application effectively and efficiently. During the use of the application, the Health Office gets results according to the expected performance targets. Although the use of the BumilKU application did not significantly reduce the maternal mortality rate in 2019, based on the aspect of monitoring the condition of pregnant women in Kulon Progo, the performance of the Health Office has improved compared to the previous year. Services for pregnant women are carried out according to procedures and received good response from the community.